Avaliação da frequência cardíaca e pressão arterial em mulheres praticantes de strong by zumba TM - Araújo de Oliveira, Milena (Educación Física y Ciencia.)
Strong by Zumba TM is a combination of high intensity training with strength exercises and basic moves aimed at a metabolic and cardiorespiratory impact. The purpose of this study was to verify heart rate and blood pressure in women during Strong by Zumba TM practice. The activities were held in a covered fair in the interior of the state of Mato Grosso, with 45 women aged 41 ± 5 who assiduously practise the dance. Blood pressure and heart rate measurements were performed before, during and after the activity. The results showed a moderate initial heart rate of 83.4 ± 17.9 bpm, an average of 135.1 ± 18.8 bpm during practice, and an average of 118.3 ± 17.9 bpm after practice, characterizing the class as of vigorous intensity. The initial arterial pressure was 88.4 ± 8.4 mmHg, during the exercise section the average was 88.6 ± 10 mmHg, and after exercise 85.1 ± 9.1 mmHg. In this study, it was observed that the regular practice of Strong by Zumba TM can contribute to the improvement of cardiovascular response and fitness, becoming a favorable modality for the health of its practitioners.